2016
DOI: 10.1016/j.jempfin.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The European sovereign debt crisis: What have we learned?

Abstract: This paper sets the background for the Special Issue of the Journal of Empirical Finance on the European Sovereign Debt Crisis. It identifies the channel through which risks in the financial industry leaked into the public sector. It discusses the role of the bank rescues in igniting the sovereign debt crisis and reviews approaches to detect early warning signals to anticipate the buildup of crises. It concludes with a discussion of potential implications of sovereign distress for financial markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The ECB has publicly stated that these policies reduce redenomination risk, and, financial market "dysfunctionality", and, most importantly, the ECBs policies may have reduced the default risk component of GIIPS sovereign yields. Kräussl et al (2016) note that the asset repurchases undertaken within the SMP in 2010-2011 had a substantial yield reduction impact, also contributing to lowering bond yield volatility and the extreme tail behavior of yield changes with substantial long-run effects, as also shown empirically by Eser and Schwaab (2016), who showed that the SMP brought large changes in bond yields upon purchase. Also, Altavilla et al (2016) examined the impact of OMT on the government bond yields and found statistically significant and economical effects on credit and, in real activity in Italy and Spain.…”
Section: 32mentioning
confidence: 78%
“…The ECB has publicly stated that these policies reduce redenomination risk, and, financial market "dysfunctionality", and, most importantly, the ECBs policies may have reduced the default risk component of GIIPS sovereign yields. Kräussl et al (2016) note that the asset repurchases undertaken within the SMP in 2010-2011 had a substantial yield reduction impact, also contributing to lowering bond yield volatility and the extreme tail behavior of yield changes with substantial long-run effects, as also shown empirically by Eser and Schwaab (2016), who showed that the SMP brought large changes in bond yields upon purchase. Also, Altavilla et al (2016) examined the impact of OMT on the government bond yields and found statistically significant and economical effects on credit and, in real activity in Italy and Spain.…”
Section: 32mentioning
confidence: 78%
“…When bank risk sharply increases, governments should issue implicit or explicit guarantees to rescue troubled banks, especially if these banks are too big to fail. This raises public debt dramatically, which has a negative impact on public finances and leads to higher sovereign risk (Gray et al 2008;Kräussl et al 2016). In addition, banking crises imply economic recessions that weaken public finances and push up sovereign risk (Angeloni and Wolff 2012).…”
Section: Contagion Between Bank and Sovereign Riskmentioning
confidence: 99%
“…Their results suggested that the banks' stock market prices and CDS spreads generally showed no reaction. Kraussl et al (2016) identified crucial events during the European sovereign debt crisis and investigated their impact on the Euro currency. They analysed how specific announcements related to vulnerable euro-zone member states, ECB actions and credit rating downgrades affected the value and the crash risk of the Euro.…”
Section: Literature Reviewmentioning
confidence: 99%